Orthopedic bioactive implants: Hydrogel enrichment of macroporous titanium for the delivery of mesenchymal stem cells and strontium. Issue 12 (2nd April 2013) - Lopa, Silvia; Mercuri, David; Colombini, Alessandra; De, Gennyfer; Segatti, Francesco; Zagra, Luigi; Moretti, Matteo
<x xml:space="preserve">Abstract</x> Insufficient implant stability is an important determinant in the failure of cementless prostheses. To improve osseointegration, we aim at generating a bioactive implant combining a macroporous titanium (TT) with a biocompatible hydrogel to encapsulate osteo‐inductive factors and osteoprogenitor cells. Amidation and cross‐linking degree of an amidated carboxymethylcellulose hydrogel (CMCA) were characterized by FT‐IR spectrometry and mechanical testing. Bone marrow mesenchymal stem cells (BMSCs) from osteoarthritic patients were cultured on CMCA hydrogels, TT, and TT loaded with CMCA (TT + CMCA) with an optimized concentration of SrCl2 to evaluate cell viability and osteo‐differentiation. Amidation and cross‐linking degree were homogeneous among independent CMCA batches. SrCl2 at 5 μg/mL significantly improved BMSCs osteo‐differentiation increasing calcified matrix (P < 0.01), type I collagen expression (P < 0.05) and alkaline phosphatase activity. TT + CMCA samples better retained cells into the TT mesh, significantly improving cell seeding efficiency with respect to TT (P < 0.05). BMSCs on TT + CMCA underwent a more efficient osteo‐differentiation with higher alkaline phosphatase (P < 0.05) and calcium levels compared to cells on TT. Based on these in vitro results, we envision the association of TT with strontium‐enriched CMCA and BMSCs as a promising strategy to generate bioactive implants promoting bone neoformation at the implant site. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3396–3403, 2013.